2018
DOI: 10.3389/frobt.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Integrated Hydraulic Smart Actuators and Smart Manifolds for High-Bandwidth Force Control

Abstract: Hydraulic actuation is the most widely used alternative to electric motors for legged robots and manipulators. It is often selected for its high power density, robustness and highbandwidth control performance that allows the implementation of force/impedance control. Force control is crucial for robots that are in contact with the environment, since it enables the implementation of active impedance and whole body control that can lead to a better performance in known and unknown environments. This paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 19 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…In some studies, it refers to actuators made of "smart materials" that have intrinsic characteristics of built-in sensors, actuators, and control mechanisms in their microstructures. In the second case, it refers to an intelligent instrument (like a DC motor or valves) that serves as an actuator in process control (Barasuol et al, 2018). Here, we will discuss smart actuators according to the second definition.…”
Section: Integration Of Signal Processing Actuation Computation Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, it refers to actuators made of "smart materials" that have intrinsic characteristics of built-in sensors, actuators, and control mechanisms in their microstructures. In the second case, it refers to an intelligent instrument (like a DC motor or valves) that serves as an actuator in process control (Barasuol et al, 2018). Here, we will discuss smart actuators according to the second definition.…”
Section: Integration Of Signal Processing Actuation Computation Anmentioning
confidence: 99%
“…Smart actuators have been widely used for the control of vehicles and robots and in the biotechnology industry (Perotti et al, 2006;Van Loon, 2015;Barasuol et al, 2018). Perotti et al (2006) reported a VHM smart actuator for a liquid hydrogen storage system, with emphasis on its self-diagnosing function.…”
Section: Integration Of Signal Processing Actuation Computation Anmentioning
confidence: 99%
“…Then combine the above two equations (Equation (16) and (17)) (14). Bring equation (18) into equation (14), and finally get the function form of parameter measurement matrix as follows. From equation (19), C θ k contains the generalized state vector χ 2 , so it is an iterative variable on the fast-varying time scale.…”
Section: B a Data-driven Multi-scale Online Joint Estimation Algorithmmentioning
confidence: 99%
“…On the basis of all measurable states, Yuan et al [15], [16] and Peran [17] have used the open-loop input and output data of electro-hydraulic system collected from the experiment to estimate the parameters of a nonlinear gray box model offline on MATLAB's System Identification Toolbox. Victor et al [18] has measured the servo spool displacement, flow and input current curves on the experimental platform and estimated the servo valve parameters (port gain) by a fitting method. Moon [19] has adopted the recurrent incremental credit assignment neural network and genetic algorithm to off-line estimate the system parameters of nonlinear electro-hydraulic servo system, such as mass, viscosity coefficient, spring constant and effective bulk modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the responsiveness of the hydraulic servo actuator to impact is poorer than that of the torque motor. To solve this problem, a new integrated smart actuator (ISA) developed by Moog in collaboration with IIT [23] has been successfully applied to the quadruped robot. Its body is additively manufactured (AM) in a titanium alloy, allowing a very compact design with integrated flow paths and wire channels.…”
Section: Introductionmentioning
confidence: 99%